Luteinizing hormone signaling is involved in synchronization of Leydig cell's clock and is crucial for rhythm robustness of testosterone production†. Issue 5 (4th February 2019) - Baburski, Aleksandar Z; Andric, Silvana A; Kostic, Tatjana S
Abstract: In mammals, circadian clock regulates concentration of many reproductive hormones including testosterone. Previously, we characterized pattern of circadian transcription of core clock genes in testosterone-producing Leydig cells. Here, the potential role of luteinizing hormone receptor (LHR)-cAMP signaling in synchronization of Leydig cell's circadian clock and rhythmic testosterone production were examined. Results showed that activation of LHR-cAMP signaling in primary rat Leydig cell culture increased Star /STAR and changed expression of many clock genes (upregulated Per1/PER1, Dec1/2, and Rorb, and downregulated Bmal1 and Rev-erba/b ). Inhibition of protein kinase A prevented LHR-triggered increase in transcription of Per1 and Dec1 . Effect of stimulated LHR-cAMP signaling on Leydig cell's clock transcription was also confirmed in vivo, using rats treated with single hCG injection. To analyze in vivo effect of low LH-cAMP activity on rhythmical Leydig cell function, rats with experimental hypogonadotropic hypogonadism were used. Characteristics of hypogonadal rats were decreased LH and testosterone secretion without circadian fluctuation; in Leydig cells decreased arrhythmic cAMP and transcription of steroidogenic genes ( Cyp11a1 and Cyp17a1 ) were observed, while decreased Star /STAR expression retains circadian pattern. However, expression of clock genes, despite changes in transcription levels (increased Bmal1, Per2, Cry1, Cry2, Rora, Rorb, Rev-erba/b /REV-ERBB, Dec1, Csnk1e, and decreased Npas2 and PER1) kept circadian patterns observed in control groups. Altogether, the results strengthened the hypothesis about role of LH-cAMP signaling as synchronizer of Leydig cell's clock. However, clock in Leydig cells is not sufficient to sustain rhythmicity of testosterone production in absence of rhythmic activity of LH-cAMP signaling. Abstract : LH-cAMP signaling is involved in synchronization of Leydig cell's circadian clock and rhythmic testosterone production